2008
DOI: 10.1371/journal.ppat.1000064
|View full text |Cite
|
Sign up to set email alerts
|

A Transgenic Drosophila Model Demonstrates That the Helicobacter pylori CagA Protein Functions as a Eukaryotic Gab Adaptor

Abstract: Infection with the human gastric pathogen Helicobacter pylori is associated with a spectrum of diseases including gastritis, peptic ulcers, gastric adenocarcinoma, and gastric mucosa–associated lymphoid tissue lymphoma. The cytotoxin-associated gene A (CagA) protein of H. pylori, which is translocated into host cells via a type IV secretion system, is a major risk factor for disease development. Experiments in gastric tissue culture cells have shown that once translocated, CagA activates the phosphatase SHP-2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
79
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(82 citation statements)
references
References 44 publications
3
79
0
Order By: Relevance
“…Grab2-associated binder (Gab), another docking protein family member, is phosphorylated on 2 tyrosine residues by the c-Met receptor tyrosine kinase (54), creating Gab1 binding motifs for SHP-2, stimulating SHP-2 phosphatase, and activating MAP kinase cascades (55). Genetic studies have suggested that CagA may show Gab-like adapter protein activity in Drosophila (56). Thus, CagA PY has striking functional similarities to p130-Cas and Gab adapter proteins, in terms of both tyrosine phosphorylation and recruitment of SH2 factors that induce downstream signaling cascades.…”
Section: Discussionmentioning
confidence: 99%
“…Grab2-associated binder (Gab), another docking protein family member, is phosphorylated on 2 tyrosine residues by the c-Met receptor tyrosine kinase (54), creating Gab1 binding motifs for SHP-2, stimulating SHP-2 phosphatase, and activating MAP kinase cascades (55). Genetic studies have suggested that CagA may show Gab-like adapter protein activity in Drosophila (56). Thus, CagA PY has striking functional similarities to p130-Cas and Gab adapter proteins, in terms of both tyrosine phosphorylation and recruitment of SH2 factors that induce downstream signaling cascades.…”
Section: Discussionmentioning
confidence: 99%
“…For example, destabilization of the E-Cadherin/β-catenin complex by CagA induces abnormal activation of the wingless/int (WNT)/ β-catenin pathway (17,18). However, the effects of CagA on tumor suppressor pathways have remained obscure.…”
mentioning
confidence: 99%
“…CagA is translocated into gastric epithelial cells through a type IV secretion system, and upon entry into cells, it causes a complex set of alterations in signal transduction (2,8,11,27,33,42,49,54,56). Many of the alterations caused by CagA are associated with malignant transformation of cells (2, 8, 11, 27-29, 33, 49, 54, 56).…”
mentioning
confidence: 99%